The Principal’s Strategy in Improving the Noble Character of Children with Special Needs at SLB Tamima Mumtaz - Imam Syuhro Wardi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the principal’s strategies in improving the noble character of students at SLB Tamima Mumtaz. This research uses a qualitative approach with a case study type to obtain in-depth and comprehensive data. Data collection techniques were carried out through observation, in-depth interviews, and documentation relevant to the research focus.The results of the study indicate that the principal has a strategic role in shaping character through various religious programs and positive habituation. In conclusion, well-planned and collaborative strategies are able to effectively improve the noble character of students.